Coastal Flora of Porbandar District, Gujarat, India - Odedra, Kunal; Shukla, Kavan; B. A. Jadeja (Annals of Arid Zone, 2024)
The coastal flora of Porbandar district, Gujarat, was studied across 23 coastal villages to assess plant diversity. Systematic field surveys recorded 213 species from 174 genera and 58 families, with dicotyledons predominating (172 species from 140 genera and 48 families) and monocotyledons comprising 41 species from 34 genera and 10 families. Comparative analysis with previous studies in Gujarat’s coastal regions revealed moderate yet significant biodiversity in Porbandar. The findings reveal diverse habitats, including beaches, mangroves, and sand dunes, each hosting unique assemblages of flora adapted to extreme coastal conditions. Among the identified species, six are classified as threatened according to the IUCN Red Data List, underscoring the urgent need for conservation efforts in this vulnerable ecosystem. The study also discusses the ongoing challenges posed by salinity and anthropogenic influences, recommending diverse native species planting strategies to enhance coastal resilience. These insights serve as a crucial baseline for future ecological studies and conservation initiatives, emphasizing the importance of preserving the coastal flora of Porbandar amidst changing environmental conditions.